Use of Mental Health Apps by Breast Cancer Patients and Their Caregivers in the United States: Protocol for a Pilot Pre-Post Study - Chow, Philip I (JMIR Res Protoc, 2019)
BACKGROUND: Over one-third of cancer patients experience clinically significant mental distress, and distress in caregivers can exceed that of the cancer patients for whom they care. There is an urgent need to identify scalable and cost-efficient ways of delivering mental health interventions to cancer patients and their loved ones. OBJECTIVE: The aim of this study is to describe the protocol to pilot a mobile app–based mental health intervention in breast cancer patients and caregivers. METHODS: The IntelliCare mental health apps are grounded in evidence-based research in psychology. They have not been examined in cancer populations. This pilot study will adopt a within-subject, pre-post study design to inform a potential phase III randomized controlled trial. A target sample of 50 individuals (with roughly equal numbers of patients and caregivers) at least 18 years of age and fluent in English will be recruited at a US National Cancer Institute designated clinical cancer center. Consent will be obtained in writing and a mobile phone will be provided if needed. Self-report surveys assessing mental health outcomes will be administered at a baseline session and after a 7-week intervention. Before using the apps, participants will receive a 30-min coaching call to explain their purpose and function. A 10-min coaching call 3 weeks later will check on user progress and address questions or barriers to use. Self-report and semistructured interviews with participants at the end of the study period will focus on user experience and suggestions for improving the apps and coaching in future studies. RESULTS: This study is ongoing, and recruitment will be completed by the end of 2018. CONCLUSIONS: Results from this study will inform how scalable mobile phone-delivered programs can be used to support breast cancer patients and their loved ones. TRIAL REGISTRATION: ClinicalTrials.gov NCT03488745; https://clinicaltrials.gov/ct2/show/NCT03488745 INTERNATIONAL REGISTERED REPORT IDENTIFIER (IRRID): DERR1-10.2196/11452